2022
DOI: 10.1590/acb370108
|View full text |Cite
|
Sign up to set email alerts
|

Ulinastatin alleviates early brain injury after traumatic brain injury by inhibiting oxidative stress and apoptosis

Abstract: Purpose: Traumatic brain injury (TBI) remains a major public health problem and cause of death. Ulinastatin (UTI), a serine protease inhibitor, has been reported to have an anti-inflammatory effect and play a role in immunoregulation and organ protection by reducing reactive oxygen species (ROS) production, oxidative stress and inflammation. However, the neuroprotective of UTI in TBI has not been confirmed. Therefore, this study aimed to investigate the neuroprotection and potential molecular mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 51 publications
(55 reference statements)
0
4
0
Order By: Relevance
“…In addition, it can treat acute inflammatory disorders, sepsis, toxic shock, and hemorrhagic shock [ 6 ]. It is reported that UTI can alleviate the cerebral ischemia-reperfusion injury by regulating inflammation and oxidative stress [ 35 ]. Another study also reported that UTI could attenuate the brain edema after intracranial hemorrhage (ICH) of male Sprague-Dawley rats and that the preliminary molecular mechanism may be related to the decrease of the expression levels of proinflammatory cytokines including IL-1 β and TNF- α [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it can treat acute inflammatory disorders, sepsis, toxic shock, and hemorrhagic shock [ 6 ]. It is reported that UTI can alleviate the cerebral ischemia-reperfusion injury by regulating inflammation and oxidative stress [ 35 ]. Another study also reported that UTI could attenuate the brain edema after intracranial hemorrhage (ICH) of male Sprague-Dawley rats and that the preliminary molecular mechanism may be related to the decrease of the expression levels of proinflammatory cytokines including IL-1 β and TNF- α [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…The mice were acclimatized for 1 week and subsequently received 3% DSS in the drinking water for 7 days, during which the mice were treated with UTI (10,000 U/kg/d) or a vehicle, weighed daily (at a similar time of day), and monitored for clinical symptoms (Figure 1). The administration dosage of UTI was determined and modified based on the prior reports of other inflammatory disease models [27,28]. The assessment of colitis severity typically is focused on body-weight loss, diarrhea, and hematochezia, which were quantified using the DAI.…”
Section: Uti Administration Ameliorated Pathological Features In Dss-...mentioning
confidence: 99%
“…TBI disturbs the balance between pro-apoptotic BAX, which forms pores in the outer mitochondrial membrane, and anti-apoptotic B cell lymphoma 2 (BCL-2), a pro-survival protein that binds to BAX (Wennersten et al, 2003;Stoica and Faden, 2010;Deng et al, 2020). Numerous natural and artificial caspase inhibitors have been identified and developed with the intention for therapeutic use in reducing neuronal cell death post TBI (Dhani et al, 2021;Feng et al, 2022;Unnisa et al, 2022).…”
Section: Cell Deathmentioning
confidence: 99%